Intrinsic DNA binding properties demonstrated for lineage-specifying basic helix-loop-helix transcription factors - Casey, Bradford H.; Kollipara, Rahul K.; Pozo, Karine; Johnson, Jane E.

(untitled) (Genome Research, 2018)
During development, transcription factors select distinct gene programs, providing the necessary regulatory complexity for temporal and tissue-specific gene expression. How related factors retain specificity, especially when they recognize the same DNA motifs, is not understood. We address this paradox using basic helix-loop-helix (bHLH) transcription factors ASCL1, ASCL2, and MYOD1, crucial mediators of lineage specification. In vivo, these factors recognize the same DNA motifs, yet bind largely different genomic sites and regulate distinct transcriptional programs. This suggests that their ability to identify regulatory targets is defined either by the cellular environment of the partially defined lineages in which they are endogenously expressed, or by intrinsic properties of the factors themselves. To distinguish between these mechanisms, we directly compared the chromatin binding properties of this subset of bHLH factors when ectopically expressed in embryonic stem cells, presenting them with a common chromatin landscape and cellular components. We find that these factors retain distinct binding sites; thus, specificity of binding is an intrinsic property not requiring a restricted landscape or lineage-specific cofactors. Although the ASCL factors and MYOD1 have some distinct DNA motif preference, it is not sufficient to explain the extent of the differential binding. All three factors can bind inaccessible chromatin and induce changes in chromatin accessibility and H3K27ac. A reiterated pattern of DNA binding motifs is uniquely enriched in inaccessible chromatin at sites bound by these bHLH factors. These combined properties define a subclass of lineage-specific bHLH factors and provide context for their central roles in development and disease.